A detailed study of leaf micromorphology and anatomy of New World Vitis L. subgenus Vitis within a phylogenetic and ecological framework reveals evolutionary convergence. Issue 4 (3rd May 2018) - Ickert‐Bond, Stefanie M.; Harris, AJ; Lutz, Sue; Wen, Jun
Abstract: We investigated leaf anatomy and micromorphology in the New World Vitis using light and scanning electron microscopy to understand the correlation of these traits to molecular phylogenetic relationships and environmental affinity. We observed traits known to differ among species of Vitis with importance in traditional taxonomy of Vitis : trichome type, stomata morphology, mesophyll organization, and midrib vascularization. We found that traits associated with water conductance and photosynthesis comprised the highest loadings of axis one of a principal components analysis (PCA) while traits related to gas exchange (i.e., the stomatal apparatus) had high loadings on axis two. Using the PCA, we identified seven clusters of species, which showed little correlation to recently reported molecular phylogenetic relationships. Moreover, analyses using Bayes Traits and Bayesian Binary Method revealed little to no phylogenetic signal in trait evolution. PCA axes one and two separated species occurring in dry southwestern North American habitats from those in mesic places. For example, a cluster of V. monticola and V. arizonica occurred adjacent to a cluster of V. californica and V. girdiana in ordination space, and the latter three species share key leaf anatomical traits. Nevertheless, among these, only V. arizonica and V. girdiana are closely related according to molecular phylogeny. Thus, the leaf micromorphological/anatomical traits of Vitis observed in this study are highly correlated with environment, but not phylogenetic relationships. We expect that trait similarities among distantly related species may result from evolutionary convergences, especially within xeric habitats of western North America.